The Bad Can Be Good: When Benign and Malicious Envy Motivate Goal Pursuit - Salerno, Anthony; Laran, Juliano; Janiszewski, Chris (Journal of Consumer Research, 2019)
AbstractBenign and malicious envy are a consequence of an unfavorable upward comparison to another individual (i.e., a negative self-other discrepancy). Benign (malicious) envy occurs when people believe the envied individual deserves (does not deserve) his/her advantage. Prior research has shown that benign envy motivates a person to address the self-other discrepancy via self-improvement, whereas malicious envy does not. This research shows that both types of envy, not just benign envy, can motivate self-improvement, provided that the opportunities to do so occur outside the envy-eliciting domain. Benign envy increases the accessibility of the belief that effort determines whether people are rewarded; hence, it motivates process-focused goal pursuit and the use of products that emphasize effort-dependent self-improvement. Malicious envy increases the accessibility of the belief that the effort does not determine whether people are rewarded; hence, it motivates outcome-focused goal pursuit and the use of products that emphasize effort-independent self-improvement. Implications and potential extensions in the areas of envy, self-conscious emotions, and goals are discussed.